Exploring infection prevention practices in home-based nursing care: A qualitative observational study. (January 2022) - Wendt, Benjamin; Huisman-de Waal, Getty; Bakker-Jacobs, Annick; Hautvast, Jeannine L.A.; Huis, Anita
Abstract: Background: Home-based nursing care continues to expand, delivering care to increasingly older clients with multiple, chronic and complex conditions that require the use of additional and more numerous invasive medical devices. Therefore, the prevention of infections poses a challenge for nurses, professional caregivers and clients. Objective: This article explores infection prevention practices and related behavioural factors in both nurses and clients to identify barriers and facilitators of infection prevention practices in home-based nursing care. Design: A qualitative, exploratory design. Setting: Four healthcare organisations providing home-based nursing care in the Netherlands. Methods: Participant observations were used as the main source of data collection complemented with focus group discussions and semi-structured interviews. Participants: Participant observations: 16 nurses, three professional caregivers and 80 clients. Semi-structured interviews: 11 clients. Focus group discussions: 15 nurses and four professional caregivers. Results: A total of 87 unique care delivery situations were observed for 55 h, complemented with three focus group discussions and 11 individual semi-structured client interviews. Infection prevention practices in home-based nursing care appeared to be challenged by 1. The specific context or environment in which the care occurred, which is more autonomous, less structured, less controlled and less predictable than other care settings; 2. Suboptimal and considerable variation in professional performance concerning the application of hand hygiene and the proper use of personal protective equipment such as face masks, barrier gowns and disposable gloves; 3. Extensive use in and outside the client's surroundings of communication devices that are irregularly cleaned and tend to interrupt nursing procedures; and 4. Inadequate organisational support in the implementation and evaluation of new information or policy changes and fragmentation, variation and conflicting information regarding professional guidelines and protocols. Conclusions: From a first-hand observational viewpoint, this study showed that the daily practice of infection prevention in home-based nursing care appears to be suboptimal. Furthermore, this research revealed considerable variation in the work environment, the application of hand hygiene, the proper use of personal protective equipment, the handling of communication devices and organisational policies, procedures and support. Finally, the study identified a number of important barriers and facilitators of infection prevention practices in the work environment, professional and team performance, clients and organisations.